PICTURESQUE IMAGES OF FELLAHS IN THE WORKS OF IVAN TRUSH - Yamash, Yuri (European Science, 2025)
The research is dedicated to the pictorial and photographic Egyptian series by Ivan Trush (1869 – 1941) executed by the Ukrainian artist during his trip to Egypt in 1912. The material examines the history and circumstances of the artist’s work on the imag